Jihadists and Weapons of Mass Destruction : a Growing Threat. - Ackerman, Gary (Taylor & Francis Ltd., 2009)
This title explores the nexus formed when malevolent actors access malignant means. Written for professionals, academics, and policymakers working at the forefront of counter terrorism efforts, "Jihadists and Weapons of Mass Destruction" is an authoritative and comprehensive work addressing the threat of weapons of mass destruction (WMD) in the hands of jihadists, both historically and looking toward the future threat environment. Providing insight on one of the foremost security issues of the 21st century, this seminal resource effectively: documents current trends in the ideology, s.